An overview of the XXI century security architecture - before and after Invasion of Ukraine - Lupu, Mădălina-Elena (Technium Social Sciences Journal, 2023)
In this article, we analyze the XXI century security architecture starting from an international security overview before the Invasion of Ukraine and ending with the one after this invasion. The research method that will be used is the comparative analysis between them. The working hypothesis refers to the Russian Federation as being the Great Power that determined a new security architecture in the XXI century, the opposite one that was designed by the Russian Federation through the Invasion of Ukraine.